Development of a Perinatal Palliative Care Model at a Level II Perinatal Center Supported by a Pediatric Palliative Care Network - Bolognani, Marco; Morelli, Paola Daniela; Scolari, Isabella; Dolci, Cristina; Fiorito, Valentina; Uez, Francesca; Graziani, Silvia; Stefani, Barbara; Zeni, Francesca; Gobber, Gino; Bravi, Elena; Tateo, Saverio; et al. (Frontiers in Pediatrics, 2021)
Objective: to describe the model build up to take care of fetuses and newborns eligible to perinatal palliative care (PnPC) followed in an Italian II level perinatal center Methods: retrospective chart review of all fetuses and newborn infants eligible to PnPC admitted to level II perinatal center within a 4 years period Results: 45 of 848 infants (0.5 %) referred to II level NICU were eligible to PnPC. 27 % had fetal diagnosis. 20 % were preterm infants at the limit of viability, 35 % were newborns with life limiting or life threatening disease diagnosed in utero or at the postnatal ward, 45 % were newborns not responding to intensive care intervention with high health care needs or medical complexity. 57 % of neonates admitted to NICU died before discharge, while 16 (35 % of population considered) were discharged home. Median age at death was 4 days after birth, and delivery room death immediately after birth occurred in 6 patients (13 %). Conclusions: Despite the paucity of our population and the high variability in disease trajectories the perinatal palliative care program build up in our region provides a reproducible method for a structured taking in charge of fetuses and neonates eligible to PnPC and their families, from the time of diagnosis to bereavement, in both outpatient and inpatient settings.